PKM Penyuluhan Kekerasan Seksual kepada Mahasiswa Program Studi Sosiologi Universitas Nusa Cendana - Pellu, Susana C. L.; Manoe, Lenny S. Bire; Ndandara, Aelsthri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
Sexual violence is an act that deprives someone of their sense of security and undermines human security. Unequal power relationships between lecturers and students often lead to sexual assault in universities. Students who were victims of sexual violence were hesitant to disclose incidences of violence on campus because they were terrified, humiliated, or unsure how to do so. The team found that students lack understanding of the concept and forms of sexual violence, are unsure of how to report violence or sexual harassment, and are not aware of the formation of a Prevention Task Force to address sexual violence in the Nusa Cendana university setting. The goal of this service project is for students to learn about the various types of sexual violence and how to report it if it occurs on campus. The service activity employs a participatory method. This activity results in the election of Anti-Sexual Violence Ambassadors who serve as champions or spokespersons for preventing and overcoming sexual violence among students, and students are becoming more conscious of all sorts of sexual violence on campus.